2013
DOI: 10.1186/1743-422x-10-251
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and hepatitis C virus

Abstract: The disproportionate imbalance between the systemic manifestation of reactive oxygen species and body’s ability to detoxify the reactive intermediates is referred to as oxidative stress. Several biological processes as well as infectious agents, physiological or environmental stress, and perturbed antioxidant response can promote oxidative stress. Oxidative stress usually happens when cells are exposed to more electrically charged reactive oxygen species (ROS) such as H2O2 or O2-. The cells’ ability to handle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
97
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 86 publications
2
97
0
7
Order By: Relevance
“…Several studies have highlighted the oxidative stress in some chronic viral infections (Oliveira et al, 2011;Paracha et al, 2013;Zhao et al, 2013), and different mechanisms for such oxidative stress have been suggested. In HIV, for example, decreased antioxidant defense and/or elevated serum levels of lipid peroxidation byproducts have been proposed (Dworkin et al, 1986;Sonnerborg et al, 1988;Revillard et al, 1992;Coodley et al, 1993;Dworkin, 1994;Favier et al, 1994;Akerlund, 1994 Schrauzer andSacher, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have highlighted the oxidative stress in some chronic viral infections (Oliveira et al, 2011;Paracha et al, 2013;Zhao et al, 2013), and different mechanisms for such oxidative stress have been suggested. In HIV, for example, decreased antioxidant defense and/or elevated serum levels of lipid peroxidation byproducts have been proposed (Dworkin et al, 1986;Sonnerborg et al, 1988;Revillard et al, 1992;Coodley et al, 1993;Dworkin, 1994;Favier et al, 1994;Akerlund, 1994 Schrauzer andSacher, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Total antioxidant capacity is a marker of antioxidant status, which may serve as an indicator of oxidant/antioxidant imbalance (Suresh et al, 2009). Different studies have addressed oxidative stress in malignancies (Rahal et al, 2014), inflammatory conditions including autoimmune diseases (Kundu et al, 2012;Norheim et al, 2012;Wakamatsu et al, 2013), as well as chronic infections such as HIV-1 (Oliveira et al, 2011), HBV (Zhao et al, 2013), and HCV (Paracha et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the tissue GSH level has been accepted as a marker for oxidative stress injury. Less tissue GSH level means more oxidative stress injury 21 . In our study, GSE treatment provides attenuation of oxidative stress injury in a cholestatic I/R injury model.…”
Section: Results Of Histopathological Analysismentioning
confidence: 99%
“…Oxidative/nitrosative stress essentially arises when the production of reactive oxygen (and nitrogen) species (ROS and RNS, respectively) exceeds cellular antioxidant defenses. HCV-induced oxidative/nitrosative stress has been observed in vivo and in vitro (5)(6)(7)(8)(9) and has been assigned to almost all HCV proteins (i.e. core, E1, E2, NS3/4A, NS4B, and NS5A) (5), with core being the most potent inducer (10,11).…”
mentioning
confidence: 99%
“…The cellular mechanisms by which HCV replication might mediate liver injury are unclear, but there is no doubt that oxidative/nitrosative stress in HCV-infected cells plays an important role in the initiation and progression of liver damage (3,5,6). Oxidative/nitrosative stress essentially arises when the production of reactive oxygen (and nitrogen) species (ROS and RNS, respectively) exceeds cellular antioxidant defenses.…”
mentioning
confidence: 99%